2022
DOI: 10.31681/jetol.1081367
|View full text |Cite
|
Sign up to set email alerts
|

Technology-based professional development program: Experiences of science teachers

Abstract: This study aimed to evaluate science teachers of gifted students who participated in a technology-based professional development program, how could be used the applications they learned in the program, and their use area for the gifted education. The case study was carried out with ten science teachers of gifted students. The data were gathered via interviews and open-ended forms and analyzed with the content analysis method. The findings showed that teachers stated that the program was beneficial for their pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…Теориялық талдау нәтижелерін қорыта келе, біз өз кезегімізде болашақ биология мұғалімдерінің кәсіби құзіреттіліктерін қалыптастыруда МТ қолданудың мазмұндық үлгісін жасақтадық (Сурет 1): Ғалымдардың пікірінше, болашақ биология мұғалімінің кәсіби құзіреттілігі, сондай-ақ танымдық, мотивациялық компоненттермен қатар, мәселелерді шешуге қажетті саналы құндылық үлгілерін қалыптастыруды талдай білу маңызды (Şule Elmalı, et al, 2022;Lavrentieva, et al, 2020;Khrolenko, et al, 2022).…”
Section: әдебиеттерге шолуunclassified
“…Теориялық талдау нәтижелерін қорыта келе, біз өз кезегімізде болашақ биология мұғалімдерінің кәсіби құзіреттіліктерін қалыптастыруда МТ қолданудың мазмұндық үлгісін жасақтадық (Сурет 1): Ғалымдардың пікірінше, болашақ биология мұғалімінің кәсіби құзіреттілігі, сондай-ақ танымдық, мотивациялық компоненттермен қатар, мәселелерді шешуге қажетті саналы құндылық үлгілерін қалыптастыруды талдай білу маңызды (Şule Elmalı, et al, 2022;Lavrentieva, et al, 2020;Khrolenko, et al, 2022).…”
Section: әдебиеттерге шолуunclassified
“…In the study conducted by Zhu, Wang, Cai & Engels (2013), it has been concluded that teachers' educational competence, social competence and technological competence are related to their innovative teaching performance. The fact that the technology proficiencies of the teachers have such a great place in the success of the education process requires that attention should be paid to the technology proficiencies in the teacher training process (Elmalı & Balkan Kıyıcı, 2022). In the study conducted by Foulger, Graziano, Schmidt-Crawford, & Slykhuis (2017), it is emphasized that education should be made according to 12 criteria related to technology proficiencies in the teacher training process.…”
Section: Teachers' Technology Proficienciesmentioning
confidence: 99%
“…Lack of proper training would, inevitably, make acquiring and maintaining CPR skills difficult. To organize effective CPR training, however, it is essential to have access to knowledgeable trainers and useful equipment (Elmali and Balkan Kiyici, 2022). Therefore, limited resources necessitate some modifications to the conventional method of CPR instruction.…”
Section: Introductionmentioning
confidence: 99%